Batam Tourism Application Based on Android Mobile - Afdhol Dzikri; Tri Ramadani Arjo (Journal of Applied Informatics and Computing, 2018)
The existence of a destination becomes one aspect of Batam City as a destination for domestic and foreign tourists. Destination places in the form of hotels, tourist destinations, sports, shopping, places of worship and tourism. This tourist destination in the metropolitan city has an important role as the heart of the city community activities. In this study discusses the use of the internet as a medium to find Batam Destination information combined by using an Android-based mobile application. The method used is Location Based Service (LBS) according to the location of the user to get the location and route to the destination of the destination in a quick and easy way. The application design phase uses some storage assistance in MySQL as a database on the webserver. This destination search application has the main feature of being able to find the closest destination location according to the user's location at that time by utilizing GPS technology. After the application is produced it will be tested with Alpha Test. The result of this research is a geographic information system application for Destinations Batam. The results of system testing indicate that this information system is feasible and can be used.